Prevalence and Pattern of Substance Use among Undergraduate Medical Students at Birat Medical College and Teaching Hospital - Shah, Rajesh Kumar; Timsinha, Sidarth; Sah, Sanjib Kumar; Mehta, Umesh Kumar; Chaudhary, Raju Kumar (Birat Journal of Health Sciences, 2021)
Introduction: Medical students encounter a constant pressure of academic and clinical activities, as well as easy access to drugs which could enable them to use different substances. Medical students who use substances can endanger others by losing sound judgment, failing to take responsibility, and causing harm to service recipients. Objective: The study was aimed to find out the prevalence and pattern of substance use among undergraduate medical students of Birat Medical College and Teaching Hospital, Nepal. Methodology: This hospital based cross sectional study was carried out from January 2021 to February 2021 at Birat Medical College and Teaching Hospital, Morang Nepal. A total of 207 subjects were included in the study, which was selected using convenience sampling. All participants were given a self-prepared semi-structured pre-tested questionnaire in order to gather information about their sociodemographic profile and pattern of substance use. Result: The overall prevalence of substance use among students of BMCTH was 59 (28.50%) (n=207). Males were significantly associated with substance use than females (P < 0.001). Prevalence of substance use were maximum among final year students 26(76.47%). The most common used substance was alcohol 49 (83.05%) followed by tobacco smoking 24 (40.67%) and cannabis 11 (18.64%).Curiosity of experience 39 (35.77%) and seeking pleasure 19 (17.43%) were the main reason of substance use among students. Conclusion: In this study students were found to be involved in some form of substance use, with many of them initiating after enrolling in medical school. Majority of students used for the sake of fun which they use as a source of entertainment to deviate their minds from the pressure of studies.